Improving Literacy of Fiqh Muamalah and Islamic Economics Through Community-Based Research Method - Alim, Muhammad Nurul; Nst, Dian Amanda; Fauzan Agung Pratama; Ikhlasul Amal Wishri; Muhammad Nugraha; Maulana Ahmad Abadi; Tri Hidayatullah; Taufik Hidayat; Wizhar Al Giffari (As-sunnah: Jurnal Pengabdian Masyarakat, 2024)
This KKNT was held in the month of Ramadhan 1445 H on 16-30 May 2024 in collaboration with the management of Al Istiqamah Mosque (BKM) in the BDSN complex Tangga Batu 1 Village, Kec. Permaksian, Kab. Toba, North Sumatra. Based on prior observation, research, and interviews, several problems were identified namely the lack of literacy in fiqh muamalat knowledge and the lack of teachers who teach children the subject of Arabic language, tahsin and tahfidh and the Koran. These problems need to be resolved by conducting programs. The method used was community-based research (CBR). The result of this community service shows that the number of communities who attended the sermons was still below expectations while the participation and enthusiasm of children in the subjects of Arabic language, tahsin and tahfidh, and the Koran was very high. This community service is expected to enhance the community literacy of fiqh muamalah and Islamic Economics. It is suggested that community awareness in learning religious knowledge must be improved to increase their participation.